Analisis Wacana Feminis Sara Mills dalam Novel Perempuan yang Menangis kepada Bulan Hitam - Rahayu, Adeledy Dwi; Rahayu, Sri (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study was conducted because many women's positions are marginalized in a text in a novel. This study aims to describe the position of the characters in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo using Sara Mills' feminist theory. This study uses a qualitative descriptive method with reading and note-taking techniques to collect data. The data source is the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo and the data obtained are in the form of quotes, both speech and narrative in the novel. The results of the study contain 64 subject-object and reader positions. The results of this study are the subject or narrator positions described in the novel are Mrs. Leba Ali, Mrs. Agustin, Magi Wara, Magi, Lawe, Leba Ali's relatives, and Mama Bernadet. While the object positions are Magi, Ina Kecil, Tara, Ama, Leba Ali, the kidnapper, Om Vincent Dangu, and the women. The reader position is to involve the reader so that they feel what the characters in the novel feel.